2008
DOI: 10.3324/haematol.12701
|View full text |Cite
|
Sign up to set email alerts
|

Acquired thrombotic thrombocytopenic purpura: ADAMTS13 activity, anti-ADAMTS13 autoantibodies and risk of recurrent disease

Abstract: © F e r r a t a S t o r t i F o u n d a t i o n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 59 publications
(69 reference statements)
0
25
0
1
Order By: Relevance
“…Prognostic factors for relapse are not well defined. Some authors have suggested that low ADAM-TS13 activity and inhibitory anti-ADAMTS13 antibodies after remission increase the risk of relapse [25,26]. In addition, Jonson et al [24] reported that severely deficient ADAMTS13 activity during the acute phase predicted relapse.…”
Section: Discussionmentioning
confidence: 98%
“…Prognostic factors for relapse are not well defined. Some authors have suggested that low ADAM-TS13 activity and inhibitory anti-ADAMTS13 antibodies after remission increase the risk of relapse [25,26]. In addition, Jonson et al [24] reported that severely deficient ADAMTS13 activity during the acute phase predicted relapse.…”
Section: Discussionmentioning
confidence: 98%
“…quinine, mitomycin, tacrolimus, sirolimus, cyclosporine), pregnancy and autoimmune diseases such as systemic lupus erythematosus. While primary or congenital cases of TTP are associated with a reduced level of ADAMTS 13, certain secondary causes of TTP may have normal levels of the enzyme [6,7]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the significance of ADAMTS13 activity and inhibitors in predicting outcomes. Most concluded that severe ADAMTS13 deficiency and the presence of antibodies against ADAMTS13 at presentation and/or remission are associated with a higher risk of disease recurrence [8,25,27]. We investigated the possibility of an association between IgG subclasses and relapse, and found that high levels of IgG 4 with undetectable IgG 1 were statistically significantly associated with a trend towards recurrence of TTP.…”
Section: Discussionmentioning
confidence: 99%